Health and Nutrition Problems Among Women in Kerala-A Review - Jacob, Divya Raichu; Poojara, Rashmi H; Daison, Oshin; M, Mikhiya; Abraham, Pretty Puthen Parampil; Thenginthodi, Shifna (Asian Journal of Biological and Life Sciences, 2025)
Health and nutrition challenges among women vary significantly across life stages, from menarche to menopause, influenced by socio-economic and lifestyle factors. Kerala, in particular, faces a high incidence of early menarche (56% of girls between 10 and 12 years), which recent studies suggest may increase the risk of early menopause and associated health concerns due to alterations in circulating hormones. This review article synthesizes current evidence on the multifaceted health and nutritional challenges affecting women in Kerala across life stages-adolescence, reproductive years, menopause, and post-menopause. Nutritional deficiencies, such as Iron Deficiency Anemia (IDA), remain a major concern, especially among vulnerable groups like tribal populations, despite interventions like the Weekly Iron Folic Acid Supplementation initiative. Concurrently, the rising prevalence of obesity-driven by sedentary lifestyles and nutrition transition has contributed to increasing rates of metabolic syndrome, particularly among urban and postmenopausal women. Reproductive health issues, including menstrual distress, Polycystic Ovarian Syndrome (PCOS), and menopause-related conditions, further compound women's health issues, significantly impacting their quality of life. The review also examines trends in health and nutrition indicators over time, using comparative analyses of NFHS-4 and NFHS-5 data, to highlight the transition in women's health status. In conclusion, the findings underscore the urgent need for targeted health policies, culturally sensitive interventions, and public health strategies to address these challenges, aiming to improve the overall well-being of women in Kerala.
Keywords: Anemia; Metabolic syndrome; NFHS; Overweight; PCOS